SQ3R model in biology education: Linking creative thinking, problem-solving, and academic achievement - Bea Hana Siswati; Erina Rizki Aulia; Eva Yunizar Yunizar; Bintang Tata Paramita Paramita; Rieziel Ann D. Bernal (Universitas Negeri Jakarta, 2026)
Creative thinking is an essential competency in biology education to support students’ problem-solving skills and learning outcomes in the 21st century. However, instructional strategies that effectively foster these abilities remain a pedagogical challenge. This study aimed to examine the relationship between creative thinking skills, problem-solving skills, and learning outcomes through the application of the Survey, Question, Read, Recite, Review (SQ3R) learning model in biology education. A correlational research design was employed involving 72 eleventh-grade students at Arjasa Public High School. Data were collected using creative thinking tests, problem-solving essay tests, and biology learning outcome assessments, and analyzed using Pearson product-moment correlation and simple linear regression. The results revealed a very strong positive correlation between creative thinking skills and problem-solving skills (r = 0.911), with creative thinking contributing 82.9% to problem-solving skills. In addition, creative thinking skills showed a strong positive correlation with learning outcomes (r = 0.613), contributing 37.5% to students’ biology learning outcomes. These findings indicate that the SQ3R learning model supports the development of creative thinking skills that are closely associated with improved problem-solving skills and learning outcomes. Therefore, SQ3R is recommended as an alternative instructional approach in biology education to promote active learning and higher-order thinking skills.